Merkel Cell Carcinoma of the Head and Neck Compared to Other Anatomical Sites in a Real-World Setting: Importance of Surgical Therapy for Facial Tumors - Kirchberger, Michael C.; Heppt, Markus V.; Schuler, Gerold; Berking, Carola; Heinzerling, Lucie (Facial Plastic Surgery, 2020)
Merkel cell carcinoma (MCC) is a rare and aggressive neuroendocrine skin tumor with a high propensity for nodal involvement, local recurrence, and distant metastases. Up to 50% of MCC arises on head and neck (HN), which may impede oncological treatment due to insufficiently wide excisions and a lower rate of sentinel lymph node detection due to more complicated lymph drainage. Several studies have compared the clinical outcome of HN-MCC with those of non-head and neck (NHN) MCC yielding inconsistent results. This single-center, retrospective analysis compared the clinical outcome of 26 HN-MCC patients with 30 NHN-MCC patients. Overall survival (OS) and disease-free survival (DFS) were calculated with the Kaplan–Meier method assuming proportional hazards. The mean resection margins were 1.6 and 2.0 cm for the HN and NHN cohort, respectively. Local relapses were more frequently observed in patients with HN-MCC (19 vs. 10%). Patients with HN-MCC had a median OS of 4.3 years compared with 7.5 years in patients with NHN-MCC (p = 0.277). The median OS by tumor stage was 11, 3, 2, and 3 years in stage I, II, III, and IV disease, respectively (p = 0.009). The median DFS in HN-MCC was 10 years and not reached in the cohort with NHN-MCC patients (p = 0.939). Our data suggest a trend toward poorer outcomes of HN-MCC compared with NHN-MCC. Patients with MCC on the head and neck carry a higher risk for local relapse, requiring resolute surgical treatment also in facial localizations at early stages.
Keywords: Merkel cell carcinoma; recurrence; survival analysis